Phenotypic variability in three families with valosin‐containing protein mutation. Issue 2 (20th August 2012) - Spina, S.; Van, A. D.; Murrell, J. R.; Hamilton, R. L.; Kofler, J. K.; Epperson, F.; Farlow, M. R.; Lopez, O. L.; Quinlan, J.; DeKosky, S. T.; Ghetti, B.
<x xml:space="preserve">Abstract</x> Background and purpose The phenotype of IBMPFD [inclusion body myopathy with Paget's disease of the bone and frontotemporal dementia (FTD)] associated with valosin‐containing protein (VCP) mutation is described in three families. Methods Probands were identified based on a pathological diagnosis of frontotemporal lobar degeneration with TDP‐43‐positive inclusions type IV. VCP sequencing was carried out. Clinical data on affected family members were reviewed. Results Ohio family: four subjects presented muscle weakness and wasting. (One subject had both neuropathic and myopathic findings and another subject showed only evidence of myopathy. The etiology of weakness could not be ascertained in the remaining two subjects.) Two individuals also showed Parkinsonism (with associated FTD in one of the two). The proband's brain displayed FTLD‐TDP type IV and Braak stage five Parkinson's disease (PD). A VCP R191Q mutation was found. Pennsylvania family: 11 subjects developed IBMPFD. Parkinsonism was noted in two mutation carriers, whilst another subject presented with primary progressive aphasia (PPA). A novel VCP T262A mutation was found. Indiana family: three subjects developed IBMPFD. FTD was diagnosed in two individuals and suspected in the third one who also displayed muscle weakness. A VCP R159C mutation was found. Conclusions We identified three families with IBMPFD associated with VCP mutations. Clinical and pathological PD was documented for the first time in members of two families. A novel T262A mutation was found. One individual had PPA: an uncommon presentation of IBMPFD.